2017
DOI: 10.1248/bpb.b16-00877
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Suppresses Osteoclast Differentiation through the Modulation of Glycosylation Including <i>O</i>-GlcNAcylation

Abstract: Osteoclasts represent the only bone resorbing cells in an organism. In this study, we investigated the effect of glucosamine (GlcN), a nutrient used to prevent joint pain and bone loss, on the osteoclastogenesis of murine macrophage-like RAW264 cells. GlcN supplementation suppressed the upregulation of osteoclast-specific genes (tartrate-resistant acid phosphatase (TRAP), cathepsin K, matrix metallopeptidase 9, and nuclear factor of activated T cell c1 (NFATc1)), receptor activator of nuclear factor-κB ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Although the underlying molecular mechanism remains undetermined, it has been indicated in previous studies that PUGNAc treatment suppresses nuclear factor-kappaB (NF-κB) signaling pathway, which is important for osteoclast differentiation. 4,11) In addition, we identified vimentin as a potential O-GlcNAcylated protein in RAW264 cells (data not shown). Since O-GlcNAc modification of vimentin affects its function and antibody against citrullinated vimentin induces osteoclastogenesis, 18,19) it is possible that O-GlcNAcylation af- fects osteoclastogenesis through the modification of vimentin; this should be investigated in the future.…”
Section: Thiamet G Suppresses Osteoclast Differentiation and Bone Resmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the underlying molecular mechanism remains undetermined, it has been indicated in previous studies that PUGNAc treatment suppresses nuclear factor-kappaB (NF-κB) signaling pathway, which is important for osteoclast differentiation. 4,11) In addition, we identified vimentin as a potential O-GlcNAcylated protein in RAW264 cells (data not shown). Since O-GlcNAc modification of vimentin affects its function and antibody against citrullinated vimentin induces osteoclastogenesis, 18,19) it is possible that O-GlcNAcylation af- fects osteoclastogenesis through the modification of vimentin; this should be investigated in the future.…”
Section: Thiamet G Suppresses Osteoclast Differentiation and Bone Resmentioning
confidence: 92%
“…Differentiated cells were subjected to TRAP staining and TRAP-positive cells containing 3 or more nuclei were counted as described previously. 11) Human male PBMCs were seeded into a 96-well cell culture plate at a density of 1 × 10 5 cells/well. After 1 d, the cells were stimulated with 25 ng/mL human M-CSF (PeproTech, Rocky Hill, NJ, U.S.A.) and 50 ng/mL sRANKL in the presence of 10 µM Thiamet G. Then the cells were further cultured for 8 d to allow differentiation.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Despite considerable knowledge of the biological activities of glucosamine (GlcN) including chondroprotective and anti-in ammatory action [1-7], its role in osteogenesis and bone tissue remains to be investigated in detail. The evidence collected so far on bone cells is mainly based on the use of monolayered non-human cell lines such as mouse MC3T3-E1 [14] and RAW 264.7 [21], fetal osteoblastic cell line hFOB1.19 [22], or animal models such as rat, mice or rabbit receiving GlcN oral administration [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that GS has a role in rebuilding the damaged cartilage by stimulating the production of proteoglycans by fibroblasts and chondrocytes [8]. Likewise, a plethora of experimental studies have demonstrated that GS can modulate the cytokine-mediated pathways regulating inflammation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%